Prevalência, mortalidade e fatores associados ao muito baixo peso ao nascer em 4 coortes de nascimentos de Pelotas, Brasil - Victora, Júlia Damiani (2018)
Prematurity is a global health problem that results in high morbidity and mortality, especially in infants born with less than 32 weeks of gestational age and weighing less than 1500 grams (very low birth weight – VLBW). Currently, prematurity is the leading cause of infant mortality and it is estimated that each year 15 million premature babies are born in the world. Health problems in short and long term are widely known in these newborns, such as pulmonary, cardiovascular, metabolic, neurological, infections, as well as vision and hearing deficiencies. Emotional and financial consequences are also being observed in these families, as well as high costs to health systems. In order to elucidate the trend over the last decades of this group of newborns, this study was carried out to verify the prevalence, mortality and association with some risk factors. For this purpose, we used data from the Pelotas birth cohorts from 1982, 1993, 2004 and 2015 that cover all live births in the city in the year in question. Each birth was computed and anthropometric measures including weight were performed. After birth a perinatal questionnaire was applied to the mothers. Mortality was identified through visits to hospitals, cemeteries and registry offices, and from 2004 on, it was evaluated through the SIM (Mortality Information System). Over these years, 225 individuals were born alive weighing <1500g, which represented our object of study. In addition to this specific group we also observed the evolution of birth prevalence by birth weight groups and neonatal mortality (up to 28 days of life) also divided by weight. The reviews of number of births and mortality were descriptive. For the contingency tables (birth weight and mortality by weight), chi-square test for proportions was used and Poisson regression with robust variance was used to correlate the risk factors. The results showed that there was a significant increase in the prevalence of VLBW from the year 2004, which remained high in 2015. A significant reduction in neonatal mortality was observed over the years, both in this specific group and in general mortality. Regarding the risk factors studied, there was a significant relation found between lower family income (mainly between the poorest 60% and the richest 40%) and VLBW but no relation was found between VLBW and maternal age or type of delivery. With this study it was possible to aggregate knowledge and demonstrate the trend of this group of newborns over 33 years and to correlate some risk factors in a medium sized city that can represent the reality of a large part of Brazil. In order to promote the reduction of the prevalence, mortality and morbidity of these newborns, investments in prevention as well as in the care of these newborns should be made. Committees and prevention protocols are being created in different parts of the world. We hope to draw attention to this group of babies, contribute with our data and influence new studies on this very relevant topic.